Ultrasonic fatigue analysis of 3D-printed carbon fiber reinforced plastic - Jung, Chang ho; Kang, Youngjae; Song, Hyunseok; Lee, Moon Gu; Jeon, Yongho (Heliyon, 2022)
The development of 3D printing technologies using composite materials has revolutionized additive manufacturing. Using these technologies, various products can be fabricated with strengths beyond the limits of the strength of the polymer used. However, although parts manufactured using carbon fiber reinforced plastic (CFRP) 3D printing have excellent characteristics, research on their durability is lacking, making their application difficult in the real industry. In this study, an ultrasonic fatigue test was conducted on a CFRP material manufactured by 3D printing to evaluate fatigue performance. Because of the characteristics of CFRP, the strength varies depending on the orientation angle of the carbon fiber, and the durability also varies. Therefore, an experiment on three types of specimens mixed in the bi-direction and uni-direction of 0° and 90° was conducted. For the ultrasonic fatigue test, a specimen design with a special shape is required according to the resonance frequency and dynamic modulus of the material. To this end, a specimen was designed based on measurements of the physical properties of the material according to the angle of the fiber, which were verified by Finite element method (FEM) modal analysis, and the fatigue life was estimated through an actual experiment. The fatigue failure life was simulated by FEM fatigue analysis considering the measured fatigue test results and the derived anisotropic properties simultaneously. Additionally, based on the advantages of CFRP 3D printing, which adjusts the fiber pattern, we fabricated a specimen with a concentric pattern to derive the fatigue life and calculate the actual life improvement. Based on the results of this study, the specific rigidity of the CFRP parts can be optimized by adjusting the fiber pattern. Additionally, the results of this study can aid in the analysis of the fatigue characteristics of 3D-printed CFRP materials.
Keywords: CFRP 3D printing; Fiber direction; Finite element method; SN curve; Ultrasonic fatigue test